A miniaturized power generation system cascade utilizing thermal energy of a micro-combustor: Design and modelling. (6th July 2017) - Meng, Long; Li, Jun; Li, Qingqing
Abstract: Currently, combustion-based micro power devices encounter the problem of low conversion efficiency. A miniaturized power generation system cascade utilizing thermal energy of a micro-combustor is proposed, because thermophotovoltaic (TPV) cells and thermoelectric (TE) modules work at different temperature levels. The system consists of a planar micro-combustor with a bended extension at the exit, two GaSb TPV modules to convert high temperature thermal radiation and two Bi–Te based TE modules attached to the bended extension to harness medium temperature thermal energy. The mathematical modelling approach to quantify the power output and conversion efficiency is systematically presented. The modelling results show that the integration of the TE modules could significantly improve the system efficiency. When burning the H2 /air mixture, the overall system efficiency could reach 2.5% under the flow condition of U 0 = 3 m/s and Φ = 1.0. Finally, measures for better thermal management to further enhance the conversion efficiency are discussed. Highlights: A miniaturized power system cascade utilizing thermal energy is proposed. High grade thermal radiation is utilized by the micro thermophotovoltaic module. Low grade thermal energy is utilized by the micro thermoelectric module. Mathematical modelling approach for the proposed system is presented. Electricity output and power generation efficiency are quantified.